Technical Report: Assessment of the Impacts of Climate Change on Human Health and Nutrition - Duante, Charmaine A.; Austria, Rovea Ernazelle G.; Borigas, John Michael E.; Acuin, Cecilia S. (2018)
Its geographic location and economic situation makes the Philippines highlyvulnerable to impacts of climate change and extreme weather events that cause considerable disruptions to food systems, affecting food security, nutrition and health especially of the most vulnerable groups. This study aims to assess the effects of exposure to extreme weather conditions, classified as natural disasters, on the proportion of households meeting the recommended energy intake (REI), and the prevalences of stunting and wasting among children under-five years old, chronic energy deficiency (CED) among lactating mothers and elderly adults and nutritionally at-risk pregnant women. This study utilized cross-sectional data from the 2013 and 2015 National Nutrition Surveys conducted nationwide by the Department of Science and Technology- Food and Nutrition Research Institute (DOST-FNRI). Exposure data came from the National Disaster Risk Reduction Management Council (NDRRMC) for typhoons and floods, the Philippine Rice Information System (PRISM) of the International Rice Research Institute (IRRI) for drought, and from the Bureau of Agricultural Statistics- Philippine Statistics Authority (BAS-PSA) for palay production. Logistic regression models were adjusted for sex, age, civil status, education, household size, work and place of work of the household head, ethnicity, illness for the past 2 weeks, avail of prenatal and mothers class for pregnant women, months of lactation for lactating mothers, hypertension for elderly, food security, membership to Philhealth, participation to Four Ps, place of residence, wealth index, palay production, and exposure to climate variables typhoons and floods one month up to six months prior to survey and drought for the first quarter of 2015 and 2016. Bivariate results showed that socioeconomic status, household size, food security status, sex, age, civil status, belonging to an indigenous group, exposure to typhoons, floods and drought had significant associations with nutrition outcomes. In full models, belonging to the poorest quintile, large and food insecure households increase the odds of stunting and wasting in children 0 to 59 months old, of chronic energy deficiency in elderly adults and lactating mothers and for pregnant women to become nutritionally at-risk . Households who are engaged in agriculture were more likely to meet the REI. The effect of exposure to typhoons and floods on meeting the REI at household level was positive at three (3) months but was negative at 6 months. Among households in the Mindanao areas, exposure to drought in either the first quarter of 2015 or 2016 only, increased the likelihood of children below five years old to become stunted and among elderly adults to become CED. However, elderly adults exposed to drought for both the first quarter of 2015 and the first quarter of 2016 made them less likely to become CED. The time of exposure to these natural 5 disasters, whether typhoons, floods or drought, appears to affect the outcomes analyzed. Cohort data would help to better understand the continuing effects of such exposures. These results provide vital inputs for more strategic responses to climate change adaptation and mitigation programs of the government particularly for vulnerable population groups.